Features of personal competence of the employees of preventive activity units of the National Police - O. Yu. Shlomin (Law and Safety, 2018)
Personal competence is considered to be the basic characteristic of a person, which allows to predict the behavior of a person in life and professional situations, therefore the purpose of the study was to study the general personal competence and specificity of the social competence of police officers of preventive activity units at different stages of the professional genesis. The methodological grounds for the study were: psychological theory of activity, the concept of genetic development of a person, modern concepts of professional genesis. The obtained results of the research should be used in drawing up programs of psychological support of police officers at different stages of professional development.